Pembekalan Kewaspadaan Sosial sebagai Penguatan Asta Cita dan Karakter Pancasila di Desa Watutulis Kabupaten Sidoarjo Jawa Timur - Prastiyono, Hendri; Huda, Mi’rojul; Swarizona, Silkania; Widodo, Bambang Sigit (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Villages hold a strategic role as engines of Indonesia’s development from the periphery, while simultaneously serving as centers of community life in the 21st century. However, the phenomenon observed in many villages—particularly in Watutulis Village, Prambon District, Sidoarjo Regency—reveals a range of potentials that can be further optimized, such as local wisdom, social capital, and community solidarity. Therefore, it is essential to provide social awareness training that emphasizes tolerance and respect for diversity within village communities. The implementation of the community service program (PKM) in Watutulis Village has brought significant benefits through the sharing of best practices. This program aims to strengthen social awareness as a foundation for promoting Asta Cita and Pancasila character values through civic training activities in Watutulis, Sidoarjo. The target participants of the program consisted of 30 individuals, including five village officials, 15 youth association members (karang taruna), and 10 local residents. The methods employed to address the partners’ challenges included dissemination, training, technology application, mentoring, and program sustainability, which were structured into two rounds of on-the-job training (OJT) and one implementation stage. The activities encompassed: (1) OJT 1: focus group discussions (FGD), Gymnastics & Outbound, and nationalistic games; (2) OJT 2: youth leadership training; and (3) Implementation: a civic-nationalistic parade. This community service initiative led to an increase in participants’ knowledge and awareness of social vigilance, which directly contributed to a deeper understanding of Asta Cita and the practical implementation of Pancasila character in daily life. Consequently, it equips the villagers of Watutulis, Sidoarjo, with social awareness to better respond to national issues. High levels of social vigilance are believed to serve as a resilient safeguard for the community, reflecting Pancasila values and encouraging the active participation of Watutulis residents at both local and regional levels.